2018
DOI: 10.1097/brs.0000000000002644
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness Matters

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Previous cadaveric studies of cervical spine have suggested that the application of anterior cervical plate could reverse the graft loads and excessively loads the bone graft in extension, but unloads the graft in flexion ( Foley et al, 1999 ; DiAngelo et al, 2000 ). Peterson et al (2018 ) used a validated custom force-sensing interbody implant to measure interbody loads in a sheep ACDF model in real time during fusion. They found that the average change in interbody force magnitude from full extension to full flexion decreased significantly during fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous cadaveric studies of cervical spine have suggested that the application of anterior cervical plate could reverse the graft loads and excessively loads the bone graft in extension, but unloads the graft in flexion ( Foley et al, 1999 ; DiAngelo et al, 2000 ). Peterson et al (2018 ) used a validated custom force-sensing interbody implant to measure interbody loads in a sheep ACDF model in real time during fusion. They found that the average change in interbody force magnitude from full extension to full flexion decreased significantly during fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the mechanical loading on the instrumentation may be a promising indicator to evaluate the fusion status after ACDF, which has the potential to advance current diagnostic methods for interbody fusion. Several animal experiments suggested that the mechanical load on the spinal instrumentation may have the potential to reflect the fusion process and evaluated the stability of implant ( Takahata et al, 2005 ; Ferrara et al, 2007 ; Ferrara et al, 2008 ; Peterson et al, 2018 ). However, the inability to precisely measure the mechanical load of interbody implant in human body remains a significant barrier to determine the feasibility of reflecting the status of fusion through load changes on the instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…This PDF file includes: Materials and Methods Fig. S1 to S14 Table S1 References (48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60) Other Supplementary Material for this manuscript includes the following:…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Many in vivo studies do not restrict the animal movement or attach invasive instruments such as rigs or jigs. Such rigs or jigs have included the manipulation of bone screws/pins to alter the position or load applied to the animal vertebrae to more accurately understand the effects of specific loads 130 but these may not represent the same loads encountered during daily activities such as walking. Furthermore, the risk of infection on open wounds and the correct positioning of mechanical test fixtures is a challenge.…”
Section: In Vivo Modelsmentioning
confidence: 99%